2013
DOI: 10.5187/jast.2013.55.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Patterns of Concentrate on Growth Performance, Blood Parameters and Carcass Characteristics in Fattening Hanwoo Cows

Abstract: This study was conducted to investigate the effects of feeding patterns of concentrates on growth performance, blood parameters and carcass characteristics in Hanwoo cows. Randomly-allocated groups, restricted concentrate feeding (T1), restricted concentrate feeding for 6 months and ad libitum 2 months (T2), restricted concentrate feeding for 4 months and ad libitum 4 months (T3), were contained with 9 animals. According to feeding patterns of concentrate, growth performance was not significantly different amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, in the present study, there was no improvement in ADG and FCR with increasing TDN levels in concentrate, and it was found to be most effective at the quantities in the T2. Lee (2017) reported that there was no difference in the ADG and FCR between the control (TDN 72.21%) and the high energy treatment (TDN 75.96%). In contrast, Ahn et al (2016) reported that the ADG and FCR of the treatments with lower TDN were better than those of the control.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in the present study, there was no improvement in ADG and FCR with increasing TDN levels in concentrate, and it was found to be most effective at the quantities in the T2. Lee (2017) reported that there was no difference in the ADG and FCR between the control (TDN 72.21%) and the high energy treatment (TDN 75.96%). In contrast, Ahn et al (2016) reported that the ADG and FCR of the treatments with lower TDN were better than those of the control.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, TDN levels of late fattening concentrates affect average daily gain (ADG) and intramuscular fat deposition of fattening cattle (Jeong et al, 2010). Therefore, it is an important factor for producing high quality meat from Hanwoo steers (Lee, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation